QPPOA : framework para qualificação do processo de produção de objetos de aprendizagem - Guterres, João Pedro Dewes (2017)
The production of learning objects allied the areas of technology and education, being a key factor to bring new possibilities of learning. Due to the increase in computational resources, the production of this type of educational material grew and began to incorporate practices of software production in general, highlighting some peculiarities due to the educational objectives proposed in the objects. Thereat, the introduction of Software Engineering practices is increasingly present in the production of learning objects, and, as in software production, the qualification of this production process has become a necessity. In software production, a consolidated solution for production qualification is in the evaluation frameworks, such as CMMI and MPS.BR. In order to think this type of solution for the production of learning objects, this research presents a framework to support the reflection on the practices performed by the centers of production of learning objects. This framework is a result of the triangulation of pertinent practices related to the theme obtained from a literature review (including a systematic review and systematic mapping) and from interviews with members of nine Brazilian learning object centers. As a result obtained after the analysis of adherence of the practices by the centers, stands out its capacity to promote the reflection of the production process, as well as well as to encourage them to carry out new practices.